Kebijakan Kriminal Terhadap Lansia Yang Berhadapan Dengan Hukum Dalam Perspektif KUHP Nasional [Criminal Policy Toward the Elderly in Conflict with the Law from the Perspective of the National Criminal Code (KUHP)] - Dudy, Aryadi Almau; Ashady, Suheflihusnaini (Indonesia Berdaya, 2025)
Abstract. This study examines the legal protection of the elderly who come into conflict with the law through the lens of substantive justice and the implementation of sentencing policies under the new Indonesian Criminal Code (KUHP). Justice, as a fundamental legal value, requires equal and proportional treatment of every individual, particularly vulnerable groups such as the elderly. In practice, elderly individuals are often subjected to legal proceedings without adequate consideration of their physical, psychological, and social limitations. However, the Human Rights Law mandates special treatment for vulnerable groups. This research employs a normative juridical method by analyzing positive legal provisions, legal principles, and legal doctrines. The findings indicate that the new Criminal Code introduces a more humane penal paradigm through the principles of corrective and rehabilitative justice. Judges play a strategic role in ensuring that sentencing for elderly offenders is carried out fairly, with personal conditions considered as mitigating factors. Thus, the sentencing approach in the new Criminal Code is expected to strengthen legal protection for the elderly and contribute to a more inclusive and just criminal justice system. Abstrak: Penelitian ini mengkaji perlindungan hukum terhadap lanjut usia (lansia) yang berhadapan dengan hukum melalui pendekatan keadilan substantif dan implementasi kebijakan pemidanaan dalam Kitab Undang-Undang Hukum Pidana (KUHP) baru. Keadilan, sebagai nilai dasar hukum, menuntut perlakuan yang setara dan proporsional terhadap setiap individu, terutama kelompok rentan seperti lansia. Dalam praktiknya, lansia sering kali diproses secara hukum tanpa mempertimbangkan keterbatasan fisik, psikologis, dan sosial mereka. Padahal, Undang-Undang Hak Asasi Manusia telah mengatur perlakuan khusus bagi kelompok rentan. Penelitian ini menggunakan metode yuridis normatif dengan menelaah ketentuan hukum positif, prinsip hukum, dan doktrin. Hasil penelitian menunjukkan bahwa KUHP baru membawa paradigma pemidanaan yang lebih humanis melalui prinsip keadilan korektif dan resosialitatif. Hakim memiliki peran strategis dalam memastikan pemidanaan terhadap lansia dilakukan secara adil dengan mempertimbangkan kondisi personal sebagai faktor yang meringankan. Dengan demikian, pendekatan pemidanaan dalam KUHP baru diharapkan dapat memperkuat perlindungan hukum bagi lansia dan mewujudkan sistem peradilan pidana yang lebih inklusif dan berkeadilan